Exploring the habitus for educational inclusion in the Lebanese context - Andary, Lara (Beirut Lebanese American University. School of Arts and Sciences. Education Department, 2013)
Exploring the Habitus for Educational Inclusion in the Lebanese Context is a study based on Bourdieu s general social theory, built around the concepts of habitus, capital, and field, and Bronfenbrenner s ecological theory. The inclusive habitus of two private schools are explored against the backdrop of marginalization of the disabled children in the broad educational system in Lebanon. One school has a declared policy of inclusion, while the other does not but accommodates the needs of mildly disabled children (MDC). The study investigates whether changing the habitus through a process of participation and cooperation amongst parents, teachers and school administration serves the inclusion of mildly disabled children (MDC), and whether teachers training matters. The study adopted a qualitative approach to answer the question to what extent are the targeted schools and their habitus supportive of the learning of MDC? Teachers, academic support teams, principals of grades 2 and 3 were interviewed; and parents of the same grade levels were asked to answer a questionnaire prepared by the researcher based on the literature review. The significant results were that to serve the process of inclusion of MDC in regular classrooms, the habitus/ecology needs to change. Teachers training was found to be an important factor that can either lead to the success or failure of inclusion as it influences the environment within their classroom. The acquisition of capital, be it linguistic, economic, social, or cultural, can play a pivotal role in the future development of the educational system and in transforming the two schools into successful inclusive environments. This study provides the ground work on which future research can be conducted to deepen the understanding of the interaction of habitus with inclusive education in Lebanon
: Mémoire
Keywords: Inclusion scolaire; School Inclusion